Geochemical response of the mid-depth Northeast Atlantic Ocean to freshwater input during Heinrich events 1 to 4. (1st November 2016) - Crocker, Anya J.; Chalk, Thomas B.; Bailey, Ian; Spencer, Megan R.; Gutjahr, Marcus; Foster, Gavin L.; Wilson, Paul A.
Abstract: Heinrich events are intervals of rapid iceberg-sourced freshwater release to the high latitude North Atlantic Ocean that punctuate late Pleistocene glacials. Delivery of fresh water to the main North Atlantic sites of deep water formation during Heinrich events may result in major disruption to the Atlantic Meridional Overturning Circulation (AMOC), however, the simple concept of an AMOC shutdown in response to each freshwater input has recently been shown to be overly simplistic. Here we present a new multi-proxy dataset spanning the last 41, 000 years that resolves four Heinrich events at a classic mid-depth North Atlantic drill site, employing four independent geochemical tracers of water mass properties: boron/calcium, carbon and oxygen isotopes in foraminiferal calcite and neodymium isotopes in multiple substrates. We also report rare earth element distributions to investigate the fidelity by which neodymium isotopes record changes in water mass distribution in the northeast North Atlantic. Our data reveal distinct geochemical signatures for each Heinrich event, suggesting that the sites of fresh water delivery and/or rates of input played at least as important a role as the stage of the glacial cycle in which the fresh water was released. At no time during the last 41 kyr was the mid-depth northeast North Atlantic dominantly ventilated by southern-sourced water. Instead, we document persistent ventilation by Glacial North Atlantic Intermediate Water (GNAIW), albeit with variable properties signifying changes in supply from multiple contributing northern sources. Highlights: We examine H1 to H4 in the mid-depth NE Atlantic (ODP 980) using εNd, B/Ca, δ 13 C and δ 18 O. Each H-event shows a unique, prominent geochemical excursion with no major influence from southern sourced water. We infer the imprint of water masses sourced from different northern hemisphere sites of subduction. Our findings may help explain why some H events show bigger climatic perturbations than others.